Giải hệ phương trình : $\left \{ {{x^2+y^2=2x} \atop {(x-1)^3+y^3=2}} \right.$ (Cho phép sử dụng máy tính bỏ túi)

Question

Giải hệ phương trình : $\left \{ {{x^2+y^2=2x} \atop {(x-1)^3+y^3=2}} \right.$ (Cho phép sử dụng máy tính bỏ túi)

in progress 0
Melanie 3 tháng 2021-09-20T00:31:23+00:00 1 Answers 7 views 0

Answers ( )

    0
    2021-09-20T00:32:59+00:00

    Đáp án:

    Giải thích các bước giải:

    \[\begin{array}{l}
    \left\{ \begin{array}{l}
    {x^2} + {y^2} = 2x\\
    {\left( {x – 1} \right)^3} + {y^3} = 2
    \end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}
    \left( {{x^2} – 2x + 1} \right) + {y^2} = 1\\
    {\left( {x – 1} \right)^3} + {y^3} = 2
    \end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}
    {\left( {x – 1} \right)^2} + {y^2} = 1\\
    {\left( {x – 1} \right)^3} + {y^3} = 2
    \end{array} \right.\\
    a = x – 1 + y;b = \left( {x – 1} \right).y\\
    \Rightarrow \left\{ \begin{array}{l}
    {a^2} – 2b = 1\\
    {a^3} – 3ab = 2
    \end{array} \right.\\
    {a^2} – 2b = 1 \Rightarrow b = \frac{{{a^2} – 1}}{2}\\
    {a^3} – 3ab = 2 \Leftrightarrow {a^3} – 3a.\frac{{{a^2} – 1}}{2} = 2\\
    \Leftrightarrow {a^3} – \frac{{3{a^3} – 3a}}{2} = 2\\
    \Leftrightarrow 2{a^3} – 3{a^3} + 3a = 4\\
    \Leftrightarrow – {a^3} + 3a – 4 = 0
    \end{array}\]

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )